Effective management of childhood constipation. Issue 11 (November 2022) - Gordon, Kim; Howarth, Lucy
Abstract: Constipation in children is a common and often difficult-to-treat functional condition. A good understanding of the causes, symptoms, and treatments are important to achieve effective management. This review highlights the pathophysiology of constipation in children and offers practical advice to healthcare professionals caring for children. We focus on possible causes, the importance of good history taking and examination to exclude treatable or causative pathology. The importance of lifestyle choices is discussed as well as guidance on treatment using laxative medication and behavioural modification.